Primary school teachers' attitudes toward distance education and motivation to teach - Kütükcü, Gülsüm; Kırkıç, Kamil Arif; Kırkıç, Kamil Arif (Bülent DİLMAÇ, 2021)
This study examines the relationship between primary school teachers' attitudes toward distance education and motivation to teach. This correlational study used the survey for collecting data from 429 primary school teachers in various regions of Turkey. The scales were transmitted to teachers via online forms. The Motivation to Teach Scale and the Attitude Scale toward Distance Learning were used for the data collection. According to the findings, primary school teachers' motivation to teach was determined to be moderately high. Also a significant difference was found in motivation to teach levels of primary school teachers in terms of variables of age, professional experience, and education status. The attitudes of primary school teachers toward distance education were determined as moderate. Besides, there was a significant difference in the attitudes toward distance education of primary school teachers depending on the variables of professional experience. There was no significant correlation between the attitudes of primary school teachers toward distance education and their motivation to teach.
1 Istanbul Sabahattin Zaim University, Faculty of Education, Istanbul, Turkey. E-mail: gulsumsahinn93@gmail.com ORCID: 0000-0002-7465-6833 2 Correspondance to: Istanbul Sabahattin Zaim University, Faculty of Education, Istanbul, Turkey. E-mail: kamil.kirkic@izu.edu.tr ORCID: 0000-0002-8902-437X
Keywords: Primary school teachers; Distance education attitude; Motivation; Motivation to teach